A special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology and a preparation method thereof
Through the cooperation of micro pore formation technology and nano-scale sepiolite, the PETG heat shrink film has been solved, with high density, poor lightness and low ultraviolet barrier rate, and a white shrink film with lightness and low density, high mechanical properties and high ultraviolet barrier is achieved.
Patent Information
- Application Number
- CN202510265009.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing PETG heat shrink film has the disadvantages of high density, poor lightness and low UV barrier rate, and is difficult to meet the needs of packaging films with good environmental protection, lightness and low density and high UV barrier.
Using micro pore formation technology, nano-scale sepiolite as a micro pore formation agent, combined with aminosilane coupling agent and epoxy chain extender, a white shrink film with light and low density, good mechanical properties and high UV barrier rate was prepared.
It achieves the thinning and density reduction of polyester films, while improving the mechanical properties and ultraviolet light barrier rate of the films, and is suitable for high-demand packaging fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a special environmentally friendly, thin, low-density white shrink film formed based on a micro-pore forming technology and a preparation method thereof, belonging to the technical field of polymer packaging materials. Background Art
[0002] In recent years, the shortage of oil resources has become increasingly obvious. Plastic products are one of the main ways to consume oil resources. However, the disposal process of plastic products after large-scale use has brought about environmental pollution problems, which has seriously affected the development and living space of various regions, countries, and even mankind. The research and application of green plastic product materials is imminent.
[0003] As the amount of PETG heat shrink film increases, its application areas become more and more extensive. In the process of PETG heat shrink film development, it must also move towards energy conservation and environmental protection, which is the inevitable way for the green development of the plastics industry. Because world resources are always a hot topic for mankind, the slogan of saving resources has gradually penetrated into people's hearts, so the development of shrink film in the direction of environmental protection is also an inevitable trend.
[0004] The density of common polyethylene terephthalate is 1.38~1.41g / cm 3 PETG heat shrink film is a kind of polymer material with relatively high density. It belongs to copolyester modified material with a density of about 1.25~1.35g / cm 3 The larger density leads to a smaller area per unit weight, which increases the cost of use and makes waste disposal more difficult. In order to reduce costs and environmental pollution, modern green and environmentally friendly packaging has proposed a development concept of thinness and lightness, which puts forward new requirements for polyester heat shrinkable film.
[0005] Chinese patent CN115742517A discloses a microporous adjustable low-density PETG heat shrinkable film and a preparation method thereof, wherein the microporous adjustable low-density PETG heat shrinkable film comprises a core layer and upper and lower surface layers, characterized in that the upper and lower surface layers mainly comprise 100 parts by mass of modified polyethylene terephthalate PETG polyester chips and 1 to 3 parts of an opening agent, and the core layer mainly comprises 100 parts by mass of PETG polyester chips, 0 to 30 parts of white masterbatch, 10 parts of PET polyester chips and 2 to 5 parts of a foaming agent; the preparation method of the above heat shrinkable film comprises mixing, extruding, melting and plasticizing, die casting, biaxial stretching, cooling and shaping, light curing, traction, trimming and winding of the raw materials to obtain the composite film. In this patent, only the core layer film has a microporous structure, which is mainly because the foaming agent is used to form holes in the patent, which greatly damages the mechanical properties of the polyester film, so the upper and lower surface layers that have not been subjected to foaming and hole forming treatment are required to enhance the overall mechanical properties. In addition, the core film foamed by the foaming agent has larger pore size and relatively higher light transmittance. Therefore, the microporous adjustable low-density PETG heat shrinkable film obtained by this patent does not have a high UV light blocking rate, so it is difficult to use in the application field of high UV blocking packaging film.
[0006] Chinese patent CN116198202A discloses a recyclable microporous PETG heat shrinkable film and a preparation method thereof, wherein the recyclable microporous PETG heat shrinkable film comprises a 5-layer structure, wherein the surface layer A and the intermediate layer B are arranged on both sides of the core layer C; the surface layer A adopts recyclable PETG polyester chips, polyglycolic acid PGA, polyepoxy chain extender ADR, and silica open smooth masterbatch; the intermediate layer B adopts recyclable PETG polyester chips and cyclic olefin porogens; and the core layer C adopts recyclable PETG polyester chips. The microporous PETG heat shrinkable film prepared by the patent has a 5-layer structure, which is very complicated, and the cyclic olefin porogen is only added to one of the 5 layers. The reduction of the overall density can only rely on the density of the microporous layer to be reduced to a very low state, so that the mechanical properties of the microporous layer are greatly reduced, and it is difficult to obtain a good high ultraviolet barrier performance as a whole.
[0007] From the above, we can see that the current PETG heat shrink film still has disadvantages such as high density, poor lightness and thinness, and low UV blocking rate. Therefore, the development of white shrink film that is environmentally friendly, light, thin, low-density, and has a high UV blocking rate is of great significance to enrich the selectivity of film materials in the packaging field. Summary of the invention
[0008] In view of the shortcomings of the above-mentioned prior art, the present invention provides a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology and a preparation method thereof, to achieve the following invention objectives: based on the micro-pore forming technology, a white shrink film with lightness, low density, good mechanical properties and high UV blocking rate is prepared.
[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology and a preparation method thereof. The raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology is, in parts by weight: 60-120 parts of pore-forming agent composite modified polyethylene terephthalate, 10-40 parts of glycol-modified polyethylene terephthalate, 5-13 parts of polybutylene terephthalate, 1~3 parts of opening lubricant, Filler 0~15 parts; The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 25-35%, and the molar percentage of diethylene glycol is 5-15%; The diol-modified polyethylene terephthalate has a glass transition temperature of 70-83° C., a melting temperature of 220-260° C., an intrinsic viscosity of 0.4-1.0 dl / g, and a number average molecular weight of 17000-21000 g / mol; The polybutylene terephthalate has a glass transition temperature of 43-50° C., a melting temperature of 220-240° C., an intrinsic viscosity of 0.6-1.0 dl / g, and a number average molecular weight of 35000-40000 g / mol; The opening lubricant is silicon dioxide with a particle size of 1 to 5 μm; The filler is one of titanium dioxide and calcium carbonate, and the particle size is 0.5-2 μm; The following are further improvements to the above technical solution: Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite After the nano-sepiolite is dried at high temperature, it is placed in a high-speed dispersion kettle, and acetone is added. After being uniformly dispersed at a high-speed dispersion rate, the dispersion rate is reduced to a low-speed dispersion rate, and an aminosilane coupling agent is added. After the low-speed dispersion and stirring reaction is completed, the modified nano-sepiolite is obtained after filtering, washing with anhydrous ethanol, and low-temperature drying; The particle size of the nano sepiolite is 10-100 nm; The aminosilane coupling agent is one of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane and N-2-aminoethyl-3-aminopropyltrimethoxysilane; The mass ratio of the nano-sepiolite, acetone and aminosilane coupling agent is 10-35:140-260:1-6; The high temperature drying, the drying temperature is 85-110°C, and the drying time is 8-15 hours; The high-speed dispersion rate is 9000-14000 rpm; The low-speed dispersion rate is 1000-2500 rpm; The low-speed dispersion stirring reaction has a dispersion rate of 1000-2500 rpm and a reaction time of 5-10 hours; The anhydrous ethanol washing is performed 2 to 4 times, and the amount of anhydrous ethanol used in each washing is 1 to 1.3 times the mass of the solid obtained by filtration; The low-temperature drying has a drying temperature of 60-80° C. and a drying time of 5-9 hours.
[0010] (2) Preparation of pore-forming agent composite modified polyethylene terephthalate Adding modified nano-sepiolite and fluorine-containing solvent into a high-speed dispersion kettle, dispersing uniformly at high speed, reducing the dispersion rate to a low speed, adding polyethylene terephthalate and epoxy chain extender, heating and maintaining the temperature to the boiling point of the fluorine-containing solvent, reacting fully under condensation reflux until the viscosity of the liquid in the kettle no longer changes, then transferring the liquid in the kettle to a centrifugal scraper film evaporator, and evaporating the fluorine-containing solvent to obtain a solid matter, which is a pore-forming agent composite modified polyethylene terephthalate; The fluorinated solvent is one of hexafluorobutanol and hexafluoroisopropanol; The epoxy chain extender is an oligomer of the BASF Joncryl® ADR series, and the specific brand is one of ADR-4400, ADR-4468, ADR-4380, and ADR-4385; The polyethylene terephthalate has a glass transition temperature of 75-85° C., a melting temperature of 250-270° C., an intrinsic viscosity of 0.5-0.7 dl / g, and a number average molecular weight of 15000-20000 g / mol; The mass ratio of the modified nano-sepiolite, the fluorinated solvent, the polyethylene terephthalate, and the epoxy chain extender is 4-9:260-580:45-120:0.5-4; The high-speed dispersion has a dispersion rate of 8000-12000 rpm; The low-speed dispersion rate is 1500-2600 rpm.
[0011] Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology (1) Melt extrusion According to the raw material formula of the special environmentally friendly, light, thin, low-density white shrink film formed based on micro-pore forming technology, all the raw materials involved in the formula are dried at 110-140° C. for 2-4 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the special environmentally friendly, light, thin, low-density white shrink film formed based on micro-pore forming technology in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 240-280° C. to melt and extrude the mixed raw materials, and the melt extruded from the die head is cooled and solidified on the surface of the casting roll to form a casting sheet, and the casting sheets of single-layer, double-layer co-extrusion, and three-layer co-extrusion structures are prepared by adjusting the number of twin-screw extruders and matching die heads; (2) Stretching The stretching comprises stretching the cast sheet using one of a uniaxial stretching process and a biaxial stretching process to obtain a base film; The uniaxial stretching process is one of longitudinal stretching and transverse stretching; The biaxial stretching process first performs longitudinal stretching and then transverse stretching; The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 85-100°C, the ratio is 1-3:1, and the tensile strength is 20-90 MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 75-140°C, and the setting time is 2-4 seconds; The transverse stretching is carried out on a transverse stretching machine, the stretching temperature is 75-135°C, the transverse stretching ratio is 2-5:1, the tensile strength is 180-200 MPa, and the stretched base film is heat-set and then cooled, the setting temperature is 50-90°C, and the setting time is 1-3 seconds; (3) Traction, trimming and winding The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind up the base film to obtain a large roll of special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology.
[0012] Compared with the prior art, the present invention achieves the following beneficial effects: 1. The present invention utilizes nano-scale sepiolite as a micro-pore-forming agent to promote the formation of microporous structure during the stretching process of polyester film. In order to ensure that the nano-scale sepiolite is dispersed in the polyester matrix at a nanometer scale, firstly, the surface of the sepiolite is modified by an aminosilane coupling agent to reduce the surface polarity of the nano-sepiolite. Secondly, the modified nano-sepiolite is first dispersed into a fluorine-containing solvent through a solvent high-speed dispersion process to ensure that the modified nano-sepiolite is dispersed into the solvent system in the form of nano-scale single particles. Then, polyester resin and epoxy chain extender are added. In the fluorine-containing solvent environment, during the reaction process of the polyester polymer chain and the epoxy chain extender, the nano-scale sepiolite is adsorbed on the polyester polymer chain segment in the form of nano-scale single particles. In addition, the amino groups on the surface of the modified sepiolite and the carboxyl groups at the ends of the polyester molecular chains have strong hydrogen bonds. The modified nano-sepiolite will be preferentially adsorbed on the end of the polyester polymer chain due to the hydrogen bonding effect. The hydroxyl functional group formed after the epoxy group is opened during the chain extension reaction of the epoxy chain extender will also utilize the hydrogen bonding effect to adsorb the modified nano-sepiolite. In the above processes, the modified nano-sepiolite will be relatively orderly dispersed in the polyester resin in the form of nano-scale single particles under the induction of hydrogen bonding adsorption. In the subsequent hot-melt film stretching process, this hydrogen bonding adsorption will enhance the bonding force between the polyester molecular chain and the nano-sepiolite. The strong bonding force will induce the formation of a small and uniform ultra-microporous structure, avoiding the appearance of larger micropores during the stretching process, thereby avoiding too much damage to the mechanical properties of the film. In addition, the ultra-microporous structure will also increase the ultraviolet light blocking rate of the film while reducing the light transmittance of the film. 2. The present invention increases the molecular weight of the polyester resin by adding an epoxy chain extender, thereby significantly improving the mechanical properties of the polyester film. In order to promote the full and thorough chain extension reaction between the epoxy chain extender and the polyester resin, the present invention avoids the melt reaction method in the conventional technology and designs a solvent reaction system so that the two polymers, polyester and epoxy chain extender, undergo chain extension reaction in a state where the molecular chain segments are fully stretched, which can ensure the high reaction rate and completeness of the reaction and achieve controllable adjustment of the chain extension reaction to a certain extent. In addition, during the reaction, the modified nano-sepiolite utilizes the strong hydrogen bond adsorption effect and is also correspondingly adsorbed in the polyester molecular chain segments in a directional manner, thereby achieving nano-scale dispersion of the nano-sepiolite in the polyester matrix resin. 3. The special environmentally friendly, thin, low-density white shrink film obtained by the present invention based on micro-pore forming technology has a thickness of 30-100 μm and a volume density of 1.04-1.17 g / cm 3 TD tensile strength is 125~132MPa, MD tensile strength is 35~48MPa, TD elongation at break is 36~40%, MD elongation at break is 209~236%, TD shrinkage is 42~73%, MD shrinkage is 1~12%, light transmittance is 16.4~19.2%, UV blocking rate is 99.1~99.5%, and dynamic friction coefficient is 0.42~0.47μs. DETAILED DESCRIPTION
[0013] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0014] Example 1: A method for preparing a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite After the nano-sepiolite is dried at high temperature, it is placed in a high-speed dispersion kettle, and acetone is added. After being uniformly dispersed at a high-speed dispersion rate, the dispersion rate is reduced to a low-speed dispersion rate, and an aminosilane coupling agent is added. After the low-speed dispersion and stirring reaction is completed, the modified nano-sepiolite is obtained after filtering, washing with anhydrous ethanol, and low-temperature drying; The particle size of the nano sepiolite is 30 nm; The aminosilane coupling agent is 3-aminopropylmethyldimethoxysilane; The mass ratio of the nano-sepiolite, acetone and aminosilane coupling agent is 25:200:3; The high temperature drying is performed at a temperature of 100°C and a drying time of 11 hours; The high-speed dispersion rate is 12000 rpm; The low-speed dispersion rate is 2000 rpm; The low-speed dispersion stirring reaction has a dispersion rate of 2000 rpm and a reaction time of 8 hours; The anhydrous ethanol washing was performed 3 times, and the amount of anhydrous ethanol used in each washing was 1.2 times the mass of the solid obtained by filtration; The low-temperature drying has a drying temperature of 70° C. and a drying time of 8 hours.
[0015] (2) Preparation of pore-forming agent composite modified polyethylene terephthalate Adding modified nano-sepiolite and fluorine-containing solvent into a high-speed dispersion kettle, dispersing uniformly at high speed, reducing the dispersion rate to a low speed, adding polyethylene terephthalate and epoxy chain extender, heating and maintaining the temperature to the boiling point of the fluorine-containing solvent, reacting fully under condensation reflux until the viscosity of the liquid in the kettle no longer changes, then transferring the liquid in the kettle to a centrifugal scraper film evaporator, and evaporating the fluorine-containing solvent to obtain a solid matter, which is a pore-forming agent composite modified polyethylene terephthalate; The fluorinated solvent is hexafluorobutanol; The epoxy chain extender is an oligomer of the Joncryl® ADR series from BASF, with a specific grade of ADR-4400; The polyethylene terephthalate has a glass transition temperature of 80° C., a melting temperature of 260° C., an intrinsic viscosity of 0.6 dl / g, and a number average molecular weight of 18000 g / mol; The mass ratio of the modified nano-sepiolite, the fluorinated solvent, polyethylene terephthalate, and the epoxy chain extender is 6:380:100:2; The high-speed dispersion has a dispersion rate of 10,000 rpm; The low-speed dispersion rate is 2000 rpm.
[0016] Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology The raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology is, in parts by weight: 100 parts of pore-forming agent composite modified polyethylene terephthalate, 20 parts of glycol-modified polyethylene terephthalate, 8 parts of polybutylene terephthalate, 2 parts of opening lubricant, 6 parts of filler; The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 30% and the molar percentage of diethylene glycol is 11%; The diol-modified polyethylene terephthalate has a glass transition temperature of 78° C., a melting temperature of 240° C., an intrinsic viscosity of 0.7 dl / g, and a number average molecular weight of 19000 g / mol; The polybutylene terephthalate has a glass transition temperature of 48°C, a melting temperature of 230°C, an intrinsic viscosity of 0.7 dl / g, and a number average molecular weight of 38000 g / mol; The opening lubricant is silicon dioxide with a particle size of 3 μm; The filler is titanium dioxide with a particle size of 1 μm; (1) Melt extrusion According to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology, all the raw materials involved in the formula are dried at 120° C. for 3 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 260° C. to melt and extrude the mixed raw materials, and the melt extruded from the die head is cooled and solidified on the surface of the casting roll to form a casting sheet, and the casting sheets of single-layer, double-layer co-extrusion and three-layer co-extrusion structures are prepared by adjusting the number of twin-screw extruders and matching die heads; (2) Stretching The stretching comprises stretching the cast sheet using a uniaxial stretching process to obtain a base film; The uniaxial stretching process is longitudinal stretching; The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 90°C, the ratio is 2:1, and the tensile strength is 60MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 100°C, and the setting time is 3 seconds; (3) Traction, trimming and winding The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind up the base film to obtain a large roll of special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology.
[0017] Example 2: A method for preparing a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite After the nano-sepiolite is dried at high temperature, it is placed in a high-speed dispersion kettle, and acetone is added. After being uniformly dispersed at a high-speed dispersion rate, the dispersion rate is reduced to a low-speed dispersion rate, and an aminosilane coupling agent is added. After the low-speed dispersion and stirring reaction is completed, the modified nano-sepiolite is obtained after filtering, washing with anhydrous ethanol, and low-temperature drying; The particle size of the nano sepiolite is 10 nm; The aminosilane coupling agent is 3-aminopropylmethyldiethoxysilane; The mass ratio of the nano-sepiolite, acetone and aminosilane coupling agent is 10:140:1; The high temperature drying, the drying temperature is 85°C, and the drying time is 8 hours; The high-speed dispersion rate is 9000 rpm; The low-speed dispersion rate is 1000 rpm; The low-speed dispersion stirring reaction has a dispersion rate of 1000 rpm and a reaction time of 5 hours; The anhydrous ethanol washing is performed twice, and the amount of anhydrous ethanol used in each washing is 1 times the mass of the solid obtained by filtration; The low-temperature drying is performed at a temperature of 60° C. and a drying time of 5 hours.
[0018] (2) Preparation of pore-forming agent composite modified polyethylene terephthalate Adding modified nano-sepiolite and fluorine-containing solvent into a high-speed dispersion kettle, dispersing uniformly at high speed, reducing the dispersion rate to a low speed, adding polyethylene terephthalate and epoxy chain extender, heating and maintaining the temperature to the boiling point of the fluorine-containing solvent, reacting fully under condensation reflux until the viscosity of the liquid in the kettle no longer changes, then transferring the liquid in the kettle to a centrifugal scraper film evaporator, and evaporating the fluorine-containing solvent to obtain a solid matter, which is a pore-forming agent composite modified polyethylene terephthalate; The fluorinated solvent is hexafluoroisopropanol; The epoxy chain extender is an oligomer of the Joncryl® ADR series from BASF, with a specific grade of ADR-4468; The polyethylene terephthalate has a glass transition temperature of 75° C., a melting temperature of 250° C., an intrinsic viscosity of 0.5 dl / g, and a number average molecular weight of 15000 g / mol; The mass ratio of the modified nano-sepiolite, the fluorinated solvent, polyethylene terephthalate, and the epoxy chain extender is 4:260:45:0.5; The high-speed dispersion has a dispersion rate of 8000 rpm; The low-speed dispersion rate is 1500 rpm.
[0019] Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology The raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology is, in parts by weight: 60 parts of pore-forming agent composite modified polyethylene terephthalate, 10 parts of glycol-modified polyethylene terephthalate, 5 parts of polybutylene terephthalate, 1 part of opening lubricant; The glycol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 25% and the molar percentage of diethylene glycol is 5%; The diol-modified polyethylene terephthalate has a glass transition temperature of 70° C., a melting temperature of 220° C., an intrinsic viscosity of 0.4 dl / g, and a number average molecular weight of 17000 g / mol; The polybutylene terephthalate has a glass transition temperature of 43°C, a melting temperature of 220°C, an intrinsic viscosity of 0.6 dl / g, and a number average molecular weight of 35000 g / mol; The opening lubricant is silicon dioxide with a particle size of 1 μm; (1) Melt extrusion According to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology, all the raw materials involved in the formula are dried at 110° C. for 2 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 240° C. to melt and extrude the mixed raw materials, and the melt extruded from the die head is cooled and solidified on the surface of the casting roll to form a casting sheet, and the casting sheets of single-layer, double-layer co-extrusion and three-layer co-extrusion structures are prepared by adjusting the number of twin-screw extruders and matching die heads; (2) Stretching The stretching comprises stretching the cast sheet using a uniaxial stretching process to obtain a base film; The unidirectional stretching process is transverse stretching; The transverse stretching is carried out on a transverse stretching machine at a stretching temperature of 75°C, a transverse stretching ratio of 2:1, and a tensile strength of 180MPa. The stretched base film is heat-set and then cooled at a setting temperature of 50°C and a setting time of 1 second. (3) Traction, trimming and winding The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind up the base film to obtain a large roll of special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology.
[0020] Example 3: A method for preparing a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite After the nano-sepiolite is dried at high temperature, it is placed in a high-speed dispersion kettle, and acetone is added. After being uniformly dispersed at a high-speed dispersion rate, the dispersion rate is reduced to a low-speed dispersion rate, and an aminosilane coupling agent is added. After the low-speed dispersion and stirring reaction is completed, the modified nano-sepiolite is obtained after filtering, washing with anhydrous ethanol, and low-temperature drying; The particle size of the nano sepiolite is 100 nm; The aminosilane coupling agent is 3-aminopropyltrimethoxysilane; The mass ratio of the nano-sepiolite, acetone and aminosilane coupling agent is 35:260:6; The high temperature drying, the drying temperature is 110°C, and the drying time is 15 hours; The high-speed dispersion rate is 14,000 rpm; The low-speed dispersion rate is 2500 rpm; The low-speed dispersion stirring reaction has a dispersion rate of 2500 rpm and a reaction time of 10 hours; The anhydrous ethanol washing was performed 4 times, and the amount of anhydrous ethanol used in each washing was 1.3 times the mass of the solid obtained by filtration; The low-temperature drying has a drying temperature of 80° C. and a drying time of 9 hours.
[0021] (2) Preparation of pore-forming agent composite modified polyethylene terephthalate Adding modified nano-sepiolite and fluorine-containing solvent into a high-speed dispersion kettle, dispersing uniformly at high speed, reducing the dispersion rate to a low speed, adding polyethylene terephthalate and epoxy chain extender, heating and maintaining the temperature to the boiling point of the fluorine-containing solvent, reacting fully under condensation reflux until the viscosity of the liquid in the kettle no longer changes, then transferring the liquid in the kettle to a centrifugal scraper film evaporator, and evaporating the fluorine-containing solvent to obtain a solid matter, which is a pore-forming agent composite modified polyethylene terephthalate; The fluorinated solvent is hexafluorobutanol; The epoxy chain extender is an oligomer of the Joncryl® ADR series from BASF, with a specific grade of ADR-4380; The polyethylene terephthalate has a glass transition temperature of 85° C., a melting temperature of 270° C., an intrinsic viscosity of 0.7 dl / g, and a number average molecular weight of 20,000 g / mol; The mass ratio of the modified nano-sepiolite, the fluorinated solvent, polyethylene terephthalate, and the epoxy chain extender is 9:580:120:4; The high-speed dispersion has a dispersion rate of 12,000 rpm; The low-speed dispersion rate is 2600 rpm.
[0022] Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology The raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology is, in parts by weight: 120 parts of pore-forming agent composite modified polyethylene terephthalate, 40 parts of glycol-modified polyethylene terephthalate, 13 parts of polybutylene terephthalate, 3 parts of opening lubricant, 15 parts of filler; The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 35% and the molar percentage of diethylene glycol is 15%; The diol-modified polyethylene terephthalate has a glass transition temperature of 83° C., a melting temperature of 260° C., an intrinsic viscosity of 1.0 dl / g, and a number average molecular weight of 21000 g / mol; The polybutylene terephthalate has a glass transition temperature of 50° C., a melting temperature of 240° C., an intrinsic viscosity of 1.0 dl / g, and a number average molecular weight of 40,000 g / mol; The opening lubricant is silicon dioxide with a particle size of 5 μm; The filler is calcium carbonate with a particle size of 2 μm; (1) Melt extrusion According to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology, all the raw materials involved in the formula are dried at 140° C. for 4 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 280° C. to melt and extrude the mixed raw materials, and the melt extruded from the die head is cooled and solidified on the surface of the casting roll to form a casting sheet, and the casting sheets of single-layer, double-layer co-extrusion and three-layer co-extrusion structures are prepared by adjusting the number of twin-screw extruders and matching die heads; (2) Stretching The stretching comprises stretching the cast sheet using a biaxial stretching process to obtain a base film; The biaxial stretching process first performs longitudinal stretching and then transverse stretching; The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 100°C, the ratio is 3:1, and the tensile strength is 90MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 140°C, and the setting time is 4 seconds; The transverse stretching is carried out on a transverse stretching machine at a stretching temperature of 135°C, a transverse stretching ratio of 5:1, and a tensile strength of 200 MPa. The stretched base film is heat-set and then cooled at a setting temperature of 90°C and a setting time of 3 seconds. (3) Traction, trimming and winding The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind up the base film to obtain a large roll of special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology.
[0023] Comparative Example 1: Based on Example 1, in step 1, in the preparation of the pore-forming agent composite modified polyethylene terephthalate, (1) the preparation of modified nano sepiolite is not performed, and in the step (2) of preparing the pore-forming agent composite modified polyethylene terephthalate, 6 parts of modified nano sepiolite are replaced by 6 parts of nano sepiolite in equal amounts. The specific operation is as follows: Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite was not performed; (2) Preparation of pore-forming agent composite modified polyethylene terephthalate The modified nano-sepiolite was replaced by 6 parts of nano-sepiolite in equal amounts, and the other operations were the same as in Example 1; The particle size of the nano sepiolite is 30 nm; Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology The operation is the same as in Example 1.
[0024] Comparative Example 2: Based on Example 1, in step 1, preparation of pore-forming agent composite modified polyethylene terephthalate, (1) preparation of modified nano sepiolite is not performed, and in (2) step of preparing pore-forming agent composite modified polyethylene terephthalate, modified nano sepiolite is not added, and 6 parts of modified nano sepiolite are replaced by 6 parts of fluorinated solvent in equal amounts. The specific operation is as follows: Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite was not performed; (2) Preparation of pore-forming agent composite modified polyethylene terephthalate The 6 parts of modified nano-sepiolite were replaced by 6 parts of fluorinated solvent, and the other operations were the same as in Example 1; Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology The operation is the same as in Example 1.
[0025] Comparative Example 3: Based on Example 1, step 1, preparation of pore-forming agent composite modified polyethylene terephthalate, (2) in the step of preparing pore-forming agent composite modified polyethylene terephthalate, no epoxy chain extender is added, and 2 parts of epoxy chain extender are replaced by 2 parts of fluorine-containing solvent in equal amounts. The specific operation is as follows: Step 1: Preparation of pore-forming agent composite modified polyethylene terephthalate (1) Preparation of modified nano-sepiolite, the operation is the same as Example 1; (2) Preparation of pore-forming agent composite modified polyethylene terephthalate The 2 parts of epoxy chain extender were replaced by 2 parts of fluorinated solvent in equal amounts, and the other operations were the same as in Example 1; Step 2: Preparation of special environmentally friendly, thin, low-density white shrink film based on micro-pore forming technology The operation is the same as in Example 1.
[0026] Performance Testing: The following performance indicators of the special environmentally friendly, thin, low-density white shrink films obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and formed based on micro-pore forming technology were tested: 1. Thickness: According to ASTM D374, the film thickness value was measured using a thickness tester (Millimar1240) produced by Mahr Company of Germany; 2. Volume density: Use the mass volume method to convert the volume density of the film; 3. Mechanical strength: tensile strength and elongation at break shall comply with ASTM D882 standard; 4. Shrinkage rate: Tested according to ASTM D1204 standard; 5. Light transmittance: According to ASTM D1003, tested with UV2600 ultraviolet spectrophotometer from Shimadzu, Japan; 6. UV blocking rate: According to ASTM D1003, tested with Nippon Denshoku NDH-5000; 7. Dynamic friction coefficient: According to ASTM D 1894, the dynamic friction coefficient of the film was measured using a friction coefficient tester produced by Blbert Instrument Company of the United States (μs); The test data is shown in Table 1: Table 1
[0027] From the data in Table 1, it can be seen that the thickness of Examples 1-3 is between 30 and 100 μm, and the volume density is all between 1.2 g / cm 3 The TD tensile strength is greater than 120MPa, the MD tensile strength is greater than 35MPa, the TD elongation at break is greater than 35%, the MD elongation at break is greater than 200MPa, the TD shrinkage is greater than 40%, the light transmittance is less than 20%, the UV light blocking rate is greater than 99%, and the dynamic friction coefficient is less than 0.5μs. From the test data of the above three embodiments, it can be seen that the low-density white shrink film obtained by the present invention has the significant advantages of being light, thin, low density, good mechanical properties, low light transmittance and high UV light blocking rate; the nano-sepiolite added in Comparative Example 1 is not surface modified, and the volume density of Comparative Example 1 is increased to 1.28g / cm3 , the tensile strength, elongation at break and shrinkage in the TD and MD directions all dropped sharply, while the light transmittance of comparative example 1 increased and the UV light blocking rate dropped significantly, which shows that it is difficult to obtain nano-scale dispersion in the polyester film matrix without surface modification of the nano-sepiolite, so it is difficult to form micropores in the film during the stretching process, and the agglomeration of the nano-sepiolite will lead to a serious decrease in the mechanical properties of the polyester film, and the light transmittance and UV blocking rate will also increase and decrease accordingly due to the failure to effectively construct a microporous structure; in comparative example 2, no modified nano-sepiolite is added, and the volume density of comparative example 2 increases to 1.31 g / cm 3 , the tensile strength, elongation at break and shrinkage in TD and MD directions increased, the transmittance increased, and the UV blocking rate decreased to 31.2%, which shows that without the addition of modified nano-sepiolite, the polyester film did not form a microporous structure, which led to a substantial increase in volume density, improved mechanical properties, increased transmittance and decreased UV blocking rate; no epoxy chain extender was added in Comparative Example 3, the volume density of Comparative Example 3 increased slightly, the tensile strength, elongation at break and shrinkage in TD and MD directions decreased to a certain extent, and the transmittance and UV blocking rate did not change much compared with Example 1, which shows that the main function of the epoxy chain extender is to improve the mechanical properties of the polyester film, and has no effect on the transmittance and UV blocking rate of the film.
[0028] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology, characterized by: The raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology is, in parts by weight: 60-120 parts of pore-forming agent composite modified polyethylene terephthalate, 10-40 parts of glycol-modified polyethylene terephthalate, 5-13 parts of polybutylene terephthalate, 1~3 parts of opening lubricant, Filler 0~15 parts; The pore-forming agent composite modified polyethylene terephthalate is prepared by: adding modified nano sepiolite and a fluorine-containing solvent into a high-speed dispersion kettle, dispersing the mixture evenly at high speed, reducing the dispersion rate to a low speed, adding polyethylene terephthalate and an epoxy chain extender, heating and maintaining the temperature to the boiling point of the fluorine-containing solvent, reacting the mixture fully under condensation reflux until the viscosity of the liquid in the kettle no longer changes, transferring the liquid in the kettle to a centrifugal scraper film evaporator, and removing the fluorine-containing solvent to obtain a solid, which is the pore-forming agent composite modified polyethylene terephthalate; The fluorinated solvent is one of hexafluorobutanol and hexafluoroisopropanol; The modified nano-sepiolite is prepared by: drying the nano-sepiolite at high temperature, placing it in a high-speed dispersion kettle, adding acetone, dispersing it uniformly at a high-speed dispersion rate, reducing the dispersion rate to a low-speed dispersion rate, adding an aminosilane coupling agent, and after the low-speed dispersion and stirring reaction is completed, filtering, washing with anhydrous ethanol, and drying at low temperature to obtain the modified nano-sepiolite.
2. The special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 1, characterized in that: The epoxy chain extender is an oligomer of the BASF Joncryl® ADR series, and the specific brand is one of ADR-4400, ADR-4468, and ADR-4380; The aminosilane coupling agent is one of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane and 3-aminopropyltrimethoxysilane.
3. The special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 1, characterized in that: The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 25-35%, and the molar percentage of diethylene glycol is 5-15%; The diol-modified polyethylene terephthalate has a glass transition temperature of 70-83° C., a melting temperature of 220-260° C., an intrinsic viscosity of 0.4-1.0 dl / g, and a number average molecular weight of 17000-21000 g / mol; The polybutylene terephthalate has a glass transition temperature of 43-50° C., a melting temperature of 220-240° C., an intrinsic viscosity of 0.6-1.0 dl / g, and a number average molecular weight of 35000-40000 g / mol; The opening lubricant is silicon dioxide with a particle size of 1 to 5 μm; The filler is one of titanium dioxide and calcium carbonate, and has a particle size of 0.5-2 μm.
4. The special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 1, characterized in that: The particle size of the nano sepiolite is 10-100 nm; The mass ratio of the nano-sepiolite, acetone and aminosilane coupling agent is 10-35:140-260:1-6.
5. The special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 1, characterized in that: The polyethylene terephthalate has a glass transition temperature of 75-85° C., a melting temperature of 250-270° C., an intrinsic viscosity of 0.5-0.7 dl / g, and a number average molecular weight of 15000-20000 g / mol; The mass ratio of the modified nano-sepiolite, the fluorine-containing solvent, the polyethylene terephthalate and the epoxy chain extender is 4-9:260-580:45-120:0.5-4.
6. The method for preparing a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 1, characterized in that: The method for preparing the special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology comprises three steps of melt extrusion, stretching, and traction, trimming, and winding; The melt extrusion is based on the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on the micro-pore forming technology. All the raw materials involved in the formula are dried at 110-140° C. for 2-4 hours, and then placed in a dry environment to cool to room temperature. Then, according to the raw material formula of the special environmentally friendly, thin, low-density white shrink film formed based on the micro-pore forming technology in parts by weight, the raw materials are mixed and put into a twin-screw extruder. The heating zones of the twin-screw extruder are heated to 240-280° C. to melt and extrude the mixed raw materials. The melt extruded from the die is cooled and solidified on the surface of the casting roller to form a casting sheet. By adjusting the number of twin-screw extruders and matching die heads, casting sheets with single-layer, double-layer co-extrusion and three-layer co-extrusion structures are prepared.
7. The method for preparing a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 6, characterized in that: The stretching comprises stretching the cast sheet using one of a uniaxial stretching process and a biaxial stretching process to obtain a base film; The uniaxial stretching process is one of longitudinal stretching and transverse stretching; The biaxial stretching process first performs longitudinal stretching and then transverse stretching; The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 85-100°C, the ratio is 1-3:1, and the tensile strength is 20-90 MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 75-140°C, and the setting time is 2-4 seconds; The transverse stretching is carried out on a transverse stretching machine, the stretching temperature is 75-135°C, the transverse stretching ratio is 2-5:1, the tensile strength is 180-200MPa, and the stretched base film is heat-set and then cooled, the setting temperature is 50-90°C, and the setting time is 1-3 seconds.
8. The method for preparing a special environmentally friendly, thin, low-density white shrink film formed based on micro-pore forming technology according to claim 7, characterized in that: The traction, trimming and winding are carried out, and the stretched base film enters the traction station. The edge device in the traction station trims the edge of the base film through a trimming knife, and then the base film is pulled to the winding machine to be wound up to obtain a large roll of special environmentally friendly, thin and low-density white shrink film formed based on micro-pore forming technology.
Citation Information
Patent Citations
Microporous adjustable low-density PETG (polyethylene terephthalate glycol) thermal shrinkage film and preparation method thereof
CN115742517A
Recyclable microporous PETG (polyethylene terephthalate glycol) thermal shrinkage film and preparation method thereof
CN116198202A
PETG blow molding film and preparation method thereof
CN101838445A
Air-permeable polyethylene film
CN108976574A
Pore-foaming agent, application of pore-foaming agent, breathable film and preparation method of breathable film
CN115678108A